Efektywność ubezpieczeniowych funduszy kapitałowych jako determinanta poziomu zabezpieczenia finansowego na okres starości - Ostrowska, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The article contains a general concept of functioning life insurance: unit-linked with capital fund. There are described the main causes of choosing this insurance. There were defined differences in worked standard to repayment part of insurance fee in depending on choosing investment fund. These funds are separated for two main reason: strategy and capital risk. (original abstract
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 2, s. 83-91